Eosinophil major basic protein activates human cord blood mast cells primed with fibroblast membranes by integrin‐β1. Issue 10 (21st September 2013) - Ben‐Zimra, M.; Bachelet, I.; Seaf, M.; Gleich, G. J.; Levi‐Schaffer, F.
Abstract Background Mast cell (MC) – eosinophil (Eos) activating cross‐talk might be critical for the severity and chronicity of allergy. Among soluble mediators, eosinophil major basic protein (MBP), a hallmark of allergy, is particularly important because it was shown to activate specific MC subtypes. We previously demonstrated that MBP activates IgE‐desensitized rat MC and human lung and cord blood‐derived MC (CBMC) after priming with fibroblast membranal stem cell factor. However, a distinct mechanism for this activation was missing. Therefore, we aimed to investigate it. Methods Major basic protein‐1 activation of CBMC primed with fibroblast‐derived membranes (FBM) was measured by β‐hexosaminidase and tryptase release. Chemical cross‐linking followed by micrometric flow cytometry probed direct interactions. Antibodies neutralized integrin‐β1 and recognized its active form. Pertussis toxin (Ptx) was used to decrease integrin‐β1 active form expression. Hematopoietic cell kinase (Hck) was identified by immunoprecipitation (IP) and silenced by siRNA. Results Major basic protein‐1‐induced CBMC activation is mediated partly by MBP1–integrin‐β1 interaction on the MC surface. FBM prime CBMC via a G protein, as confirmed by Ptx, to shift integrin‐β1 to its active form. Following MBP1 binding, integrin‐β1 binds Hck that further transduces the activation signal. MC priming with FBM leads to up‐regulation in Hck protein level. MC integrin‐β1 neutralization inhibits MBP1‐induced activation and uptake. Hck silencing results with reduced MBP1‐induced activation. Conclusions Fibroblast‐derived membranes, integrin‐β1, and Hck are involved in MBP1‐induced activation of CBMC and therefore represent a distinct mechanism for this activation. This finding might implicate integrin‐β1 and Hck as targets for decreasing MC – Eos activating cross‐talk in allergy.